Integration of economic intelligence and knowledge management in the decision-making process - HACHICHA, Ahmed; BEKRI, Mouna (Turkish Economic Review, 2019)
Abctract. The fact that a company’s performance and efficiency are related to the decision-making process requires a considerable amount of up-to-date, relevant and high quality data, information and knowledge. This paper is a theoretical research based on various studies about knowledge management processes, economic intelligence and the relationships between them, as well as their practices within companies and their integration into the decision-making process in order to ensure the sustainability of the company and its economic development. This paper proposes a knowledge-based approach to analyze the decision making process. More precisely, it is used to assess the importance of information and the decision making criteria. Keywords. Economic intelligence, Knowledge management, Decision making. JEL. A12, D01, D81, D91, E71.